A model to estimate the lifetime of structures located in seismically active regions. (15th July 2020) - Lopez-Caballero, F.; Aristizábal, C.; Sánchez-Silva, M.
Highlights: Simplified model assessing lifetime evolution of structures in seismic regions is done. The model overcomes the mathematical complexities used in analytical solutions. A model easily to implement with a great potential to be used in engineering practice. The model assumptions are flexible enough to accommodate various modeling needs. A model assessing the cumulative damage in structures due to randomly shock sequences. Abstract: Understanding and modeling the evolution of structural systems throughout time, especially by considering its cumulative damage, is a key point for risk decision making. This concept is of extreme importance for design criteria definition, operational policies, robust life-cycle cost estimations and real time-dependent vulnerability assessment. In particular, an important objective of these type of analyses, is the estimation of the structure lifetime distribution and its corresponding mean time to failure (MTTF). However, analytic solutions of these two main concepts are not an easy task. Therefore, it is necessary to develop new approaches that can be used to better approximate the lifetime of structures in an accurate and useful way for engineering purposes. Within this context, the objective of this research work is to present a methodology to estimate the lifetime distribution of structures, and the derived properties of a structural system located in a seismic region. Mainshocks are modelled as a homogeneous Poisson process with constant mean rate of occurrence. The model, assumes that the deterioration of a given structure is mainly controlled by the cumulative damage generated by a set of consecutive earthquake events in a certain period of time. This approach can be easily implemented and provides a good estimation of the lifetime distribution of a structure, without venturing into the mathematical complexities of an analytic solution but retaining the main features of the system performance. Finally, an illustrative practical case at a real site is provided.